Cryptocaryon irritans recombinant proteins as potential antigens for sero-surveillance of cryptocaryonosis - Lokanathan, Yogeswaran; Mohd Adnan, A.; Kua, Bc; Nathan, Sheila (Wiley, 2016)
Cryptocaryonosis is a major problem for mariculture, and the absence of suitable sero-surveillance tools for the detection of cryptocaryonosis makes it difficult to screen Cryptocaryon irritans-infected fish, particularly asymptomatic fish. In this study, we proposed a serum-based assay using selected C. irritans proteins to screen infected and asymptomatic fish. Eight highly expressed genes were chosen from an earlier study on C. irritans expressed sequence tags and ciliate glutamine codons were converted to universal glutamine codons. The chemically synthesized C. irritans genes were then expressed in an Escherichia coli expression host under optimized conditions. Five C. irritans proteins were successfully expressed in E. coli and purified by affinity chromatography. These proteins were used as antigens in an enzyme-linked immunosorbent assay (ELISA) to screen sera from experimentally immunized fish and naturally infected fish. Sera from both categories of fish reacted equally well with the expressed C. irritans recombinant proteins as well as with sonicated theronts. This study demonstrated the utility of producing ciliate recombinant proteins in a heterologous expression host. An ELISA was successfully developed to diagnose infected and asymptomatic fish using the recombinant proteins as antigens.